2014
DOI: 10.14814/phy2.12237
|View full text |Cite
|
Sign up to set email alerts
|

Rates of carbon monoxide elimination in males and females

Abstract: The purpose of this study was to verify the previously reported shorter half‐time of elimination (t½) of carbon monoxide (CO) in females compared to males. Seventeen healthy subjects (nine men) completed three sessions each, on separate days. For each session, subjects were exposed to CO to raise the carboxyhemoglobin percentage (COHb) to ~10%; then breathed in random order, either (a) 100% O2 at poikilocapnia (no CO2 added), or (b) hyperoxia while maintaining normocapnia using sequential gas delivery, or (c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In a study examining this gender differences in CO t 1/2 disappeared when tHb‐mass was normalized suggesting that CO storage explained much of the difference (Zavorsky et al. ). Due to the low number of female subjects within the study it is impossible to conclude further than this.…”
Section: Discussionmentioning
confidence: 96%
“…In a study examining this gender differences in CO t 1/2 disappeared when tHb‐mass was normalized suggesting that CO storage explained much of the difference (Zavorsky et al. ). Due to the low number of female subjects within the study it is impossible to conclude further than this.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that women had a shorter half-life of CO elimination than men. The factors found to influence the rate of CO elimination were V A and total haemoglobin mass [20].…”
Section: Sexmentioning
confidence: 98%
“…In many disease-related studies, we could find demographic factors that may be relevant to the disease [17,18]. In some studies, age and sex were reported to relate to the rate of CO uptake and elimination [19,20].…”
Section: Demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations